Morphological Characteristics and Diseases of Soy Plants - Gafurova Ominakhon; Sodikova Maftuna; Teshajonova Makhliyo; Tukhtasinov Farkhod; Sultonov Davron (Genius Journals, 2023)
This article presents information about the morphological characteristics of soybean (Glycine maxim), its role in the food industry, its biological classification, and its cultivation.
Keywords: Legumes; protein; lysine